Polymerization-Induced Polymersome Fusion - Varlas, Spyridon (J Am Chem Soc, 2019)
[Image: see text] The dynamic interactions of membranes, particularly their fusion and fission, are critical for the transmission of chemical information between cells. Fusion is primarily driven by membrane tension built up through membrane deformation. For artificial polymersomes, fusion is commonly induced via the external application of a force field. Herein, fusion-promoted development of anisotropic tubular polymersomes (tubesomes) was achieved in the absence of an external force by exploiting the unique features of aqueous ring-opening metathesis polymerization-induced self-assembly (ROMPISA). The out-of-equilibrium tubesome morphology was found to arise spontaneously during polymerization, and the composition of each tubesome sample (purity and length distribution) could be manipulated simply by targeting different core-block degrees of polymerization (DPs). The evolution of tubesomes was shown to occur via fusion of “monomeric” spherical polymersomes, evidenced most notably by a step-growth-like relationship between the fraction of tubular to spherical nano-objects and the average number of fused particles per tubesome (analogous to monomer conversion and DP, respectively). Fusion was also confirmed by Förster resonance energy transfer (FRET) studies to show membrane blending and confocal microscopy imaging to show mixing of the polymersome lumens. We term this unique phenomenon polymerization-induced polymersome fusion, which operates via the buildup of membrane tension exerted by the growing polymer chains. Given the growing body of evidence demonstrating the importance of nanoparticle shape on biological activity, our methodology provides a facile route to reproducibly obtain samples containing mixtures of spherical and tubular polymersomes, or pure samples of tubesomes, of programmed length. Moreover, the capability to mix the interior aqueous compartments of polymersomes during polymerization-induced fusion also presents opportunities for its application in catalysis, small molecule trafficking, and drug delivery.